Analysis of Learning Interest Indonesian - Indar Listia Ningsih; Eka Titi Andaryani (International Journal of Educational Technology Research, 2023)
This study aims to find out information related to the learning interests of fifth grade students at SDN Banjaranyar 01 , Brebes Regency . This study uses a qualitative descriptive research method. Data collection techniques in this study, namely observation, interviews, and documentation. Data analysis techniques use the Miles and Huberman model. Based on the results of the study, it was concluded that (1) there is a link between interest and learning outcomes obtained by fifth grade students, namely already satisfactory as evidenced by the acquisition of scores above the KKM in the student master book. High learning outcomes are influenced by students' interest in learning Indonesian; (2) there are factors that cause interest in learning, namely internal factors from within students' self-intentions to learn Indonesian. While external factors from the outside are influenced by various teacher teaching methods, family environmental conditions that pay little attention to student learning styles, and the lack of completeness of infrastructure in schools; (3) the teacher's efforts to increase interest in learning Indonesian by holding literacy culture habituation before learning activities begin for fifteen minutes and the teacher directs students who have problems in reading comprehension to go to the library accompanied by the BP teacher.